Studying how a mathematics teacher’s professional identity shapes and is shaped by the use of digital resources in the classroom - Krog Skott, Charlotte; Psycharis, Giorgos (NOMAD Nordic Studies in Mathematics Education, 2024)
Teachers face many issues when trying to integrate digital resources (DR) into mathematics classes. This article applies an identity-based perspective to understand teachers’ roles in the practices that evolve in such classes. We focus on Victor, a Greek mathematics teacher, who, when viewed from levels beyond the classroom, experienced to become a reform-oriented teacher and a designer of DR. We explore how these experiences of professional identity shapes and is shaped by his work with DR at the classroom level. We show how Victor’s identity changed from ”being a mathematics teacher who struggles with inquiry-based teaching” to ”becoming a mathematics teacher who uses DR to support inquiry-based learning” and outline what fuelled these changes. Our results suggest that it is important to connect an identity perspective with classroom interactions and mathematics.